2019
DOI: 10.2147/ijn.s193624
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhanced growth and differentiation of myoblast cells grown on E-jet 3D printed platforms</p>

Abstract: BackgroundSkeletal muscle tissue engineering often involves the prefabrication of muscle tissues in vitro by differentiation and maturation of muscle precursor cells on a platform which provides an environment that facilitates the myogenic differentiation of the seeded cells.MethodsPoly lactic-co-glycolic acid (PLGA) 3D printed scaffolds, which simulate the highly complex structure of extracellular matrix (ECM), were fabricated by E-jet 3D printing in this study. The scaffolds were used as platforms, providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…In order to mimic the extracellular environment and the native cellular morphology, the main bioengineering strategy is focused on the 3D encapsulation of muscular cell precursors in biocompatible materials. In the last years, 3D bioprinting, 43 54 hydrogel molding, 55 59 and microporous scaffolds 60 62 have been implemented to fabricate skeletal muscle tissues.…”
Section: D Engineering For Skeletal Muscle Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to mimic the extracellular environment and the native cellular morphology, the main bioengineering strategy is focused on the 3D encapsulation of muscular cell precursors in biocompatible materials. In the last years, 3D bioprinting, 43 54 hydrogel molding, 55 59 and microporous scaffolds 60 62 have been implemented to fabricate skeletal muscle tissues.…”
Section: D Engineering For Skeletal Muscle Culturementioning
confidence: 99%
“…To mimic the extracellular matrix, poly lactic-co-glycolic acid (PLGA) multilayered scaffolds were made with E-jet 3D printing. 53 By comparing different fibrilar gaps in the scaffolds, the authors concluded that 50 µm gaps enhance cell adhesion and proliferation. In all the previous works, the bioprinting design was based on lines or meshes to guide the alignment of myotubes.…”
Section: D Engineering For Skeletal Muscle Culturementioning
confidence: 99%
“…3D printed scaffolds with defined mechanical properties have been designed to guide cellular growth and differentiation, [67] and substrate topography can stimulate actin filament alignment within single cells [68] and enhance tissue maturation. [69] While it has been shown that both the rigidity and the shape of the ECM influences cell development, both aspects have not yet been optimized within the same in vitro assay.…”
Section: Tunable High-precision Scaffolds For Myoblast Actin Fiber Almentioning
confidence: 99%
“…The spatial arrangement, porosity, biocompatibility, and proper scale of the ECM are some of the most important features that must be adjusted for use in nervous tissue, skin, bone, and muscle [ 76 ]. Nevertheless, several other factors, such as mechanical properties and chemical modification of scaffolds, significantly influence cellular behavior [ 5 , 87 ].…”
Section: Polysaccharide-based Porous Materials For Tissue Engineermentioning
confidence: 99%